A phage display‐selected peptide inhibitor of Agrobacterium vitis polygalacturonase. (18th September 2015) - Warren, Jeremy G.; Kasun, George W.; Leonard, Takara; Kirkpatrick, Bruce C.
Summary: A grobacterium vitis, the causal agent of crown gall of grapevine, is a threat to viticulture worldwide. A major virulence factor of this pathogen is polygalacturonase, an enzyme that degrades pectin components of the xylem cell wall. A single gene encodes for the polygalacturonase gene. Disruption of the polygalacturonase gene results in a mutant that is less pathogenic and produces significantly fewer root lesions on grapevines. Thus, the identification of peptides or proteins that could inhibit the activity of polygalacturonase could be part of a strategy for the protection of plants against this pathogen. A phage‐displayed combinatorial peptide library was used to isolate peptides with a high binding affinity to A . vitis polygalacturonase. These peptides showed sequence similarity to regions of O ryza sativa (EMS66324, Japonica) and T riticum urartu (NP_001054402, wild wheat) polygalacturonase‐inhibiting proteins (PGIPs). Furthermore, these panning experiments identified a peptide, SVTIHHLGGGS, which was able to reduce A . vitis polygalacturonase activity by 35% in vitro . Truncation studies showed that the IHHL motif alone is sufficient to inhibit A . vitis polygalacturonase activity.